Necesidad de incorporar en el código orgánico integral penal, las circunstancias agravantes del delito de sicariato - Cabrera Ramón, Ismael Patricio (2017)
Within the scope of the Ecuadorian criminal procedural law, the legal concept of contract killings as a crime, which in its concept proposed in the Organic Integral Penal Code provides as follows: "The person who kills another by price, payment, reward, promise, remuneration or other form of benefit, for himself or a third party, shall be punished by deprivation of liberty for a term of 22 to 26 years. The same penalty shall be applicable to the person, which directly or by brokerage, order or order the cometimiento of this illicit trafficking. It is understood that the offense was committed in Ecuadorian territory and jurisdiction when the acts of preparation, organization and planning, are made in Ecuador, even when their implementation is consumed in the territory of another State. The single advertising or offer of contract killings, shall be punished by deprivation of liberty for a term of five to seven years," however there is no feature that in addition to being the payment for the death of a person, causing serious inconsistencies with the provisions raised within the same legal body. (Organic Integral Penal Code, 2014). Art. 143. Among which we have to affect the principle of due process, and even the principle of innocence of the people in this type of crime are being accused, because being accused, the process that will be followed and the aggravating circumstances are not well specified in the aforementioned legal body, causing it to criminalize or confused with another type of crime either the same murder in itself because the same penalty is applied in these two offenses without aggravating circumstances to identify the two as such, or at least special feature in which it can be to criminalize the hired killers. In the same way we have in the case of the murder because in its relevant article mentions "the man who kills another shall be punished by deprivation of liberty for a term of ten to thirteen years", which in this case the only differentiation with the hired killers would be the death penalty and the form of payment key feature of hired killers, but it is not clear, nor a way of among these three items, so as to identify them with clarity or precision. (Organic Integral Penal Code, 2014). Art. 144. With what is given also to the violation of the principles of implementation of the rights according to the provisions of article 11, paragraph 1, of the Constitution of our country, taking into account how particularly in the area of constitutional provisions, as the Ecuadorian State would be admitting his responsibility, by a judicial error or violation of the Agreement as set out in article 11 paragraph 9 paragraph 4, which would be responsible directly if there is an error, if it be the case within the theme of the hired killers. It should be emphasized that the hired killers is a growing phenomenon that has a high degree of violence, which generates a strong social impact and that now it is taking into consideration on the part of our authorities, since it recognized the existence of the hired killers that when you had one of these cases judged as "aggravated homicide", leaving to take into account people who spoke to this crime is carried out, this gave as a result the impunity of war crimes committed. It is important then to say that the characterization of this offense is now taken as a figure dependent like others, that sustains a process as a mechanism, a tool by which this may be punished according to the circumstances not so clear referred to in the present article that typifies this crime and therefore commit error of any kind at the time of the trial, you can resort to take it as another type of crime or worse to follow a process not suitable, for the unequivocal evidence that they are presented or by implication, it would lead to a confusion of crime and responsibility.